A Unique Glycine-Rich Motif at the N-terminal Region of Bamboo mosaic virus Coat Protein Is Required for Symptom Expression - Ping Lan; Wen-Bin Yeh; Chih-Wei Tsai; Na-Sheng Lin (Molecular Plant-Microbe Interactions, 2010)
The coat proteins (CP) of many plant viruses are multifunctional proteins. We used N-terminal sequencing and mass spectrometry/mass spectrometry analysis to identify a truncated form of the Bamboo mosaic virus (BaMV) CP missing the N-terminal 35 amino acids (N35). The N35 region is unique in the potexviruses by its containing a glycine-rich motif (GRM) not present in databases but highly conserved among BaMV isolates. Results from site-directed mutagenesis and deletion mutational analysis showed that loss of this region converted necrotic local lesions to chlorotic local lesions on Chenopodium quinoa leaves. Furthermore, this region is required for successful development of mosaic symptoms on Nicotiana benthamiana leaves but is dispensable for BaMV replication and cell-to-cell and long-distance movement as well as virion assembly. This unique GRM-containing region of BaMV CP may be a symptom determinant in specific hosts.